"Both masters and victims of their times": Engaging aporetic time in Midnight's Children. (June 2015) - O'Brien, Sean P.
Time in Salman Rushdie's Midnight's Children is characterized by a cacophony of representational forms that the narrator Saleem uses with and against each other, such as cyclical time, timelessness, and revisionary linear historical time. Existing analyses of the novel's representations of time have generally concluded that one or another of the competing temporal frameworks in the novel is primary and that Rushdie and Saleem ultimately discard or subordinate the others. On the contrary, the novel denies a single coherent temporal structure and instead focuses on productively engaging the diversity of time in keeping with Paul Ricoeur's theory of aporetic time. Ricoeur theorizes that every framework of representing time includes aporias, blind spots it can't satisfactorily address, and he argues that we must explore these tensions in representations of time — a task for which narrative is uniquely helpful. Investigating aporetic time in Midnight's Children develops our understanding of Ricoeur by providing a representation of aporetic time to supplement and challenge Ricoeur's theoretical model (and Homi K. Bhabha's thoughts on narrating the nation). Midnight's Children 's narratorial ambivalence and multivalence with regard to temporal frameworks is closely tied to the novel's major thematic concerns: constructing an understanding of oneself, one's nation, and history in the face of conflicting experiences and imperfect narratives of significant and traumatic personal and historical events. Applying Rushdie and Ricoeur to each other productively develops our understanding of how complex, contradictory narrative representations of time and of identities can provide a way forward for individuals and nations between the twin dangers of tyrannical narrative orthodoxy and impotent relativism.